Determination of groundwater quality using geochemical methods in densely populated housing in Kubang Jaya Village, Siak Hulu District, Kampar Regency - Juandi Muhammad; Winda Pangesti (Science, Technology, and Communication Journal, 2024)
The determination of groundwater quality in dense residential housing in Kubang Jaya Village, Siak Hulu District, Kampar Regency has been carried out using physical and chemical parameters. This study aims to determine the quality of groundwater by taking samples of borehole water. Sampling was carried out at Ginting Housing; the number of samples taken was 17, and the distance between each sampling point was around 200 m. Parameters analyzed to test groundwater quality were turbidity, conductivity, pH, and total dissolved solids (TDS). Based on the results of groundwater quality tests in terms of turbidity level parameters, the average value was 2.0 NTU, conductivity was 191.7 ppm, pH was 4.28, and TDS was 132.4 mg/l. Overall, the results of the water quality test in this research area are unfit for consumption because they are too acidic, but they are still safe and suitable for daily needs.